The influence of green perceived value and green awareness on purchasing decisions through purchase interest - Alamsyah, Muhammad Hafizh; Salim, Muhartini (Gema Wiralodra, 2024)
Awareness of sustainable purchasing decisions. This study uses quantitative methods with an associative descriptive approach and data processing using the PLS-SEM 4 application. The research population includes consumers of Alfamart customers in Bengkulu who have purchased environmentally friendly shopping bags. The questionnaire was distributed to 100 respondents. The results showed a significant influence between Green Perceived Value and Green Awareness on purchasing decisions for environmentally friendly shopping bags through purchase interest based on simultaneous and partial hypothesis testing. The study concludes that Green Perceived Value and Green Awareness significantly influence Purchase Interest and Purchasing Decisions related to environmentally friendly shopping bags. The findings emphasize the importance of incorporating environmental values, increasing consumer awareness, and generating buying interest in marketing strategies. Future research should expand sample coverage and consider additional factors like socio-economic variables, consumer preferences, and specific marketing strategies influencing purchase decisions for such products. These findings have practical implications for manufacturers and marketers, suggesting the importance of integrating environmental values into marketing strategies to increase consumer awareness and foster buying interest in eco-friendly products. The results offer valuable guidance for designing effective strategies that align with consumer preferences for sustainability. Future research should expand sample coverage and consider additional factors, such as socio-economic variables, to refine marketing approaches for environmentally friendly products further.